A universal strategy for fabrication and morphology control of polyoxometalate-based metal–organic frameworks. Issue 11 (16th January 2020) - Li, Xiao-Hui; Liu, Yi-Wei; Lu, Ying; Zhang, Zhong; Tian, Hong-Rui; Liu, Shu-Mei; Liu, Shu-Xia
Abstract : Fabrication of POM@MOFs by utilizing the oxidization of POMs to metals and the effect of polyoxoanion charge on POM@MOF morphology. Abstract : A novel method is proposed to fabricate polyoxometalate-based metal–organic frameworks (POM@MOFs) by using the ability of POMs to oxidize metals to cations. The morphology-controlled growth of POM@MOFs (NENU- n 3 ) is achieved in the absence of any modulators and an effect of polyoxoanion charge number on morphology is observed.